T. SHEVCHENKO’S CREATIONS IN THE ART OF LITERARY COMPOSITION - Kukuruza, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article reveals mastery of literary compositions which were created by experts of the theatrical art of Ukraine on the ground of Taras Shevchenko’s poetry and biography.